Membangun Integritas Anak: Kontribusi Keluarga dan Sekolah dalam Upaya Pendidikan Anti Korupsi - Zainudin Hasan; Ganesya Ganesya (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Children's integrity is an important aspect that must be built from an early age to prevent corrupt behavior in the future. Family and school are the main factors that have a very important role in building a child's integrity. The family as the first unit has the responsibility to set an example of good character by instilling the values ​​of honesty, responsibility and discipline through open communication. On the other hand, schools act as a formal environment that not only teaches the academic curriculum, but also provides character education and equips children with an understanding of ethics and morality. This research uses a qualitative approach by interviewing parents and teachers and analyzing various literary sources such as books, journals, and so on. The research results show that this collaboration not only increases awareness of the importance of integrity, but also reduces the potential for corrupt behavior.